Cost-Utility Study of Warfarin Genotyping in the VACHS Affiliated Anticoagulation Clinic of Puerto Rico - Martes-Martinez, Carlos; Méndez-Sepúlveda, Cristian; Millán-Molina, Joel; French-Kim, Matthew; Marín-Centeno, Heriberto; Rivera-Miranda, Giselle C.; Hernández-Muñoz, José J.; Duconge-Soler, Jorge (Puerto Rico Health Sciences Journal, 2017)
Objective: To evaluate the cost-utility of the pharmacogenetic-guided dosing of warfarin (PGx), when compared to the current dosing strategy. Methods: A Markov model was developed to assess the impact of the genotypingguided warfarin dosing in a hypothetical cohort of patients. The model was based on the percentage of time patients spent within the therapeutic international normalized ratio (INR) range (PTTR). PTTR estimates and genotype distribution were derived from a cohort of patients (n = 206) treated in the Veteran Affairs Caribbean Healthcare System (VACHS) and from results of other research study. Costs, utilities and event probability data were obtained from the literature. Probabilistic and one-way sensitivity analyses were performed to explore the range of plausible results. Willingness to pay was established at $50,000 per Quality Adjusted Life Year (QALY) gained. Results: According to our model, the PGx strategy showed a QALY increase of 0.0021, with an increase in total cost of $272. This corresponds to an incremental cost-utility ratio (ICUR) of $127,501, ranging from $95,690 to $148,611. One-way sensitivity analysis revealed that the ICURs were more sensitive to the cost of genotyping and the effect of genotyping on the PTTR. Conclusion: Our model suggests that the warfarin PGx was not superior to the standard of care dosing strategy in terms of cost-utility.